Experimental thermal storage research of organic binary phase change materials in building environment. Issue 11 (2nd September 2017) - Lv, Yajun; Jin, Weizhun; Yang, Yan; Zhang, Haibin; Zhang, Xinzhong; Ding, Fangyi; Zhou, Weibing
ABSTRACT: This paper aims to reveal the heat transfer mechanism of low-temperature phase change material (PCM) and design PCM heat storage device in building heating environment. Firstly, low-temperature binary PCMs of lauric acid and stearic acid are prepared, and their thermal properties are investigated by DSC. Then, shell and tube latent heat thermal energy storage units are conducted, and heat transfer experiments are carried out to analyze the heat transfer mechanism of PCM. The results demonstrate that natural convection plays an important role in heat transfer process, and the heat storage efficiency of PCMs can be significantly enhanced by increasing the fin width and improving the inlet heat transfer fluid (HTF) temperature. Furthermore, some proposals are put forward to guide the design of PCM storage device in building heating environment.